Behavioral Neurobiology of Aging - Pardon, Marie-Christine; Bondi, Mark W. (Current Topics in Behavioral Neurosciences,, 2012)
The increased life expectancy seen in the past century constitutes an unprecedented economic challenge to modern societies.  Public health perspectives aside, people do not want to simply live longer; they want to age successfully and remain physically and mentally active in their later years.  Major advances in our understanding of brain aging and, in particular, the distinction between normal and pathological aging are required before this goal is realized.  This volume discusses the current state of research findings related to healthy brain aging by integrating human clinical studies and translational research in animal models.  Several chapters offer a unique overview of successful aging, age-related cognitive decline and its associated structural and functional brain changes, as well as how these changes are influenced by reproductive aging.  Insights provided by preclinical studies in mouse models and advanced neuroimaging techniques in humans are also presented.  Another series of chapters specifically discuss the distinction between normal aging and Mild Cognitive Impairment, a frequent precursor of dementia, the recent advances made through both epidemiological and neuroimaging studies, and the research challenges to be addressed before we can accurately predict progression to dementia among those older adults who are at risk.  The book also covers medical and psychiatric conditions, such as cerebrovascular diseases and depression, that can negatively impact cognition.  It closes with a presentation of strategies to diminish and delay age-related cognitive declines, both pharmacological and non-pharmacological.  This volume provides topics that will be useful to researchers, clinicians and students interested in the current knowledge and research challenges in neurobiological perspectives in aging as well as future research directions in aging research.